Mineral resources in Iceland coal mining - Pokorný, Richard 1978-; Fialová, Veronika 1988-; Grimsson, Friðgeir 1976-; Koutecký, Vít (Cambridge Scholars Publisher, 2021)
iceland is known as â oethe land of fire and iceâ . Those who come to know this country intimately, however, can see that even the islandâ (TM)s inhabitants are full of fire. They are hearty, honest, and proud of their ancestors. This book is dedicated to the Icelandic men and women involved in prospecting and mining of Icelandic coal deposits during the First and Second World Wars. Their effort helped the nation survive cruel periods of war and commercial blockades. The book is the first to provide a self-contained overview of the history of coal mining in Iceland, including extensive introductory chapters on the geology of the island and the origin of coal-bearing formations. The histories of exploratory works, mining methods, and mining companies also find their place in the book. The focal point, however, lies in the description of individual coal mines, ranging from the largest systems of adits and galleries of commercial origin to small pits utilized by local farmers. Besides its historical-economic aspect, the book will be of great significance for the support of geoheritage and the promotion and protection of inanimate nature. It will appeal to a wide range of readers, such as historians, anthropologists, geologists, paleontologists, climatologists, and the general public interested in the history and nature of this beautiful Nordic country.
Keywords: Mineralogie; Kohlenbergbau; Island; Coal mines and mining / Iceland / History / 20th century; World War, 1914-1918 / Iceland; World War, 1939-1945 / Iceland; Coal mines and mining; Iceland; 1900-1999; Mining industry; Mining technology; History